Lap shear test for solder materials: Local stress states and their effect on deformation and damage. (June 2020) - Siroky, Georg; Magnien, Julien; Melinc, David; Kozeschnik, Ernst; Kieslinger, Dietmar; Kraker, Elke; Ecker, Werner
Abstract: This work presents a detailed analysis of stress states and different strain measures of two lap-shear sample designs. The stress- and strain distribution are discussed for both sample designs through numerical simulation. Additionally in-situ measurements of lap-shear experiments are performed to compare the large strain and damage behavior of the different sample designs. Despite the use of in-situ video-extensometer strain measurements, a deviation among elastic moduli from tensile- and lap-shear experiments is observed. Finite element analysis reveals that inhomogeneous strains due to boundary effects are the reason for the observed moduli deviation. A strain correction method is presented to correct video-extensometer measurements. The parameters of the correction function were obtained from numerical simulation and are provided for several sample dimensions. To illustrate the effectiveness of the proposed strain correction method, the correction function is applied to experimental lap-shear test data. The corrected shear moduli compare well with shear moduli calculated from tensile tests reported in literature. Graphical abstract: Unlabelled Image Highlights: Numerical study of local stresses and stress state in lap shear test Experimental investigation of deformation and damage Numerical investigation of strain measures in lap-shear test Correction method to obtain objective shear moduli